2010
DOI: 10.1177/1538192710371982
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis of a Measure of “Mentoring” Among Undergraduate Students Attending a Hispanic Serving Institution

Abstract: The present study validated the underlying domains that comprise the mentoring experiences of students attending a Hispanic Serving Institution. Mentoring was hypothesized to comprise four interrelated components as measured by the College Student Mentoring Scale. T test results indicated different groups of students received similar mentoring experiences, whereas confirmatory factor analyses revealed the mentoring model was valid. The factor structure was found to be significantly different between White and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Moreover, our review advances understanding of how different groups of students and mentors may perceive mentoring differently (e.g., Crisp, 2009;Crisp & Cruz, 2010;Hu & Ma, 2011;Mekolichick & Gibbs, 2012). …”
Section: Contributions Of the Present Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, our review advances understanding of how different groups of students and mentors may perceive mentoring differently (e.g., Crisp, 2009;Crisp & Cruz, 2010;Hu & Ma, 2011;Mekolichick & Gibbs, 2012). …”
Section: Contributions Of the Present Reviewmentioning
confidence: 97%
“…Similarly, research by Crisp (2009) revealed that various forms of mentoring support proposed by Nora and Crisp (2007) may be experienced differently between White, Hispanic, and African American students attending a community college. Further, research by Crisp and Cruz (2010) conducted at a 4-year Hispanic Serving Institution found that mentoring was experienced differently by White and Hispanic students, as evidenced by a significantly different factor structure.…”
Section: Perceptions Functions and Roles Of Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies document that integrated mentoring expands a mentees' network, sense of self-empowerment, and overall academic and career preparation (Luna & Prieto, 2012). Crisp and Cruz (2012) distinguish four types of support: emotional, educational and career related, knowledge of academics, and role modeling.…”
Section: Mentoringmentioning
confidence: 99%
“…In turn, sense of belonging has also been shown to promote Latinx student academic achievement at HSIs (Chun, Marin, Schwartz, Pham, & Castro-Olivo, 2016). However, it is essential to note conceptual differences on perceptions of mentoring between Latinx and students from other racial groups in a survey of students at an HSI, which suggests a need for measures designed for different groups of students (Crisp & Cruz, 2010). Furthermore, it is critical to assess if Latinx students are engaging in academic enrichment opportunities, such as bridge or research and internship programs, and how these experiences further empower them.…”
Section: Campus Climatementioning
confidence: 99%